Environmental cadmium exposure alters the internal microbiota and metabolome of Sprague–Dawley rats - Liu, Songqing; Deng, Xin; Li, Zheng; Zhou, Wenjing; Wang, Gang; Zhan, Jiasui; Hu, Binhong (Frontiers in Veterinary Science, 2023)
Cadmium (Cd) is a toxic element that can negatively affect both humans and animals.It enters the human and animal bodies through the respiratory and digestive tracts, following which it tends to accumulate in different organs, thereby seriously affecting human and animal health, as well as hampering social and economic development. Cd exposure can alter the composition of intestinal microbiota. In addition, it can damage the peripheral organs by causing the translocation of intestinal microbiota. However, the relationship between translocation-induced changes in the composition of microbiome in the blood and metabolic changes remains unclear. In the present study, we investigated the effects of Cd exposure on microbiota and serum metabolism in rats by omics analysis. The results demonstrated that Cd exposure disrupted the balance between the blood and intestinal flora in Sprague-Dawley (SD) rats, with a significant increase in gut microbiota (Clostridia_UCG_014, NK4A214_group) and blood microbiome (Corynebacterium, Muribaculaceae). However, Cd exposure caused the translocation of Corynebacterium and Muribaculaceae from the gut into the blood. In addition, Cd exposure was associated with the up-regulation of serum indoxyl sulfate, phenyl sulfate, and p-cresol sulfate; down-regulation of δ-tocopherol and L-glutamine; and changes in blood microbiome and metabolites. In conclusion, we identified novel metabolic biomarkers for Cd toxicity, which will also expand our understanding of the role of blood microbiome in Cd-induced injury.